Komunikasi Dan Kepuasan Pasien Pada Pelayanan Kebidanan Saat Pandemi Di Puskesmas Socah - Rodiyatun Rodiyatun; Siti Anisak; Vera Yuliana Sukma (FORIKES, 2022)
The Covid-19 pandemic has an impact on all aspects of life, especially in the health care system. Health protocols in suppressing decline have changed the communication patterns of health workers and patients. Communication is one of the factors that is often considered as the source of conflict that triggers patient dissatisfaction with the health service. The purpose of this study was to analyze the relationship of midwife communication skills with patient satisfaction levels during the pandemic. The type of research is analytics, with a cross-sectional design. Variable dependent is communication skills and independent variable is the level of satisfaction. The population is new patients in The Mother and Child Division at Socah community health center, with the criteria of 25 - 35 years old. The type of sampling used probability sampling, with systematic sampling techniques based on the register of visits in October 2020, the number of samples as many as 216 people. Data collection using questionnaires. The results of data collection consist of an overview of the research site, general data, and special data. In variable Satisfaction, Level is Satisfied as much as 65.43%, Quite Satisfied as much as 19.75% and Less Satisfied as much as 14.82%. Rank Spearman test results obtained ρ